2009
DOI: 10.1016/j.neuron.2008.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Postmating Behavioral Switch in Drosophila Females by Internal Sensory Neurons

Abstract: SUMMARY Mating induces changes in the receptivity and egg-laying behavior in Drosophila females, primarily due to a peptide pheromone called sex peptide which is transferred with the sperm into the female reproductive tract during copulation. Whereas sex peptide is generally believed to modulate fruitless-GAL4-expressing neurons in the central nervous system to produce behavioral changes, we found that six to eight sensory neurons on the reproductive tract labeled by both ppk-GAL4 and fruitless-GAL4 can sense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
375
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(398 citation statements)
references
References 28 publications
(43 reference statements)
13
375
1
Order By: Relevance
“…In studies on Drosophila ovulation, female postmating behavior, and male courtship or reproductive behavior (Hasemeyer et al, 2009;Lee et al, 2001;Monastirioti, 2003;Yang et al, 2009), abdominal peripheral neurons were observed to directly project to the abdominal ganglion to mediate diverse functions. Therefore, although it is not yet clear what functions the Grs are mediating in the multidendritic neurons and reproductive organs, it seems likely that the information sensed by the Grs in these organs is conveyed to the abdominal ganglion to be processed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies on Drosophila ovulation, female postmating behavior, and male courtship or reproductive behavior (Hasemeyer et al, 2009;Lee et al, 2001;Monastirioti, 2003;Yang et al, 2009), abdominal peripheral neurons were observed to directly project to the abdominal ganglion to mediate diverse functions. Therefore, although it is not yet clear what functions the Grs are mediating in the multidendritic neurons and reproductive organs, it seems likely that the information sensed by the Grs in these organs is conveyed to the abdominal ganglion to be processed.…”
Section: Discussionmentioning
confidence: 99%
“…Based on expression pattern, it seems likely that the neurons expressing these Grs could function in regulation of accessory gland secretion in males or regulation of ovulation in females. Also, female postmating behavior is regulated upon detection of male sex peptide by receptors in sensory neurons innervating the female genital tract (Hasemeyer et al, 2009;Yang et al, 2009), suggesting that Gr-expressing neurons innervating the reproductive organs may have similar functions. Although sex-specific expression was not observed for any of the Gr-GAL4 drivers, it seems plausible that second order neurons may confer specificity in relaying information to higher centers, similar to what has been proposed for Gr32a (Koganezawa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed the requirement for a subset of afferent ventral nerve cord interneurons that express apterous (ap) and project to central parts of the brain [20]. Other attempts to map the neuronal circuitry mediating the SP response used membrane-bound SP (mSP) or RNAi knock-down of SPR in restricted patterns [21][22][23][24]. These studies identified three restricted neuronal expression patterns, where SPR expression in SPR mutants can restore, or expression of mSP can induce the SP response.…”
Section: Introductionmentioning
confidence: 99%
“…These neurons are defined by the expression of the sex-determination genes doublesex (dsx) and fruitless ( fru), and of pickpocket ( ppk), a DEG/ENaC channel involved in nociception [21,22,24,25]. In both the central nervous system and PNS, dsx and fru are expressed in approximately 700 and approximately 2000 neurons, respectively, in characteristic patterns, while ppk is expressed exclusively in a subset of peripheral nervous system (PNS) neurons [21,24,[26][27][28]. Overlapping expression of these three genes has been identified in a subset of genital tract neurons that project to central areas of the brain suggesting that these neurons signal the presence of SP to higher order processing centres in the brain [21,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…At least for egg production and receptivity changes, SP acts through its receptor, sex peptide receptor (SPR), which is expressed in neurons throughout the body of the female (Yapici et al, 2008). Previous work found that a set of SPR þ neurons that innervate the female reproductive tract and express the genes pickpocket and fruitless are necessary and sufficient for these changes (Hasemeyer et al, 2009;Yang et al, 2009). In an interesting talk, Carolina Rezaval (University of Oxford) described how several of these essential neurons share circuitry with neurons expressing the sex determination gene, doublesex.…”
mentioning
confidence: 99%